EFEK APLIKASI SERICIN PADA HIDROKSIAPATIT TERHADAP PERLEKATAN SEL OSTEOBLAS - Siti Sunarintyas; Yeni Yustisia; Alva Edy Tontowi (Jurnal Teknosains, 2011)
Hydroxyapatite (HA) is often used as a human bone graft. Modification of HA surface is developed to increase osseointegration process which is influenced by cells attachment surrounded the tissue. Sericin has polar side groups which accelerate cells attachment. The aim of this research was to determine the effect of sericin application over HA surface on the attachment of osteoblast cells. The research used HA synthesized from gypsum (Kulon Progo, Yogyakarta). Sericin was extracted from silkworm cocoons of Bombyx mori. Sericin of 0.01, 0.05, 0.1% were applied over HA discs surface (10 mm in diameter, 3 mm thick). The discs were inserted into osteoblast cells culture of MC3T3E1 for attachment test. The data were analyzed by ANOVA and LSD. The result showed that the amount of osteoblast cells attached to HA (7.60±0.42) was significantly difference (p<0.05) with HA + sericin 0.01% (10.30±0.52), HA + sericin 0.5% (10.63±0.70), HA + sericin 0.1% (10.67±0.87). Variation of sericin concentrations applied over HA did not influence any significant difference on the amount of cells attachment (p>0.05). In conclusion, sericin application over HA surface increased the amount of osteoblast cells attachment. Concentrations of sericin application over HA (0.01, 0.05, 0.1%) did not influence osteoblast cells attachment.